THE INFLUENCE OF PROMOTION ON INTEREST IN BECOMING A CUSTOMER IN THE SUMEDANG SANTRI SYARIAH PAWNSHOP UNIT - Adi Rohendi; Ihwan Suparman; Eka Abdul Hamid (STAI Sebelas April Sumedang, 2024)
Islamic pawnshops are financial institutions that operate in accordance with Islamic principles. Islamic pawnshops offer a variety of financial services, including collateral-based loans, gold trading, and asset management, all of which are carried out in accordance with Islamic principles. Islamic pawnshops function as economic drivers in Indonesia by providing easily accessible and affordable financial services for individuals and small businesses. However, many people still do not know the products and services available at Islamic pawnshops, the majority of people only know that the products at Islamic pawnshops are only pawns, for this reason, promotional activities are needed to inform the public about the types of products and services available at Islamic pawnshops. This study aims to determine the effect of promotion on interest in becoming customers at the Islamic pawnshop unit of Santri Sumedang. This study uses a quantitative approach with a descriptive verification method (explanatory). The sample in this study amounted to 88 subjects. While the data collection technique used a questionnaire. The data analysis technique is by analysis in the form of validity and reliability tests, descriptive analysis and inferential statistical analysis. The results of the study indicate that promotion has a positive effect on interest in becoming a customer. This is evidenced by the significance level value of 0.000 <0.05 so that it can be concluded that the research hypothesis is accepted. Therefore, it can be concluded that promotion can have a significant effect on interest in becoming a customer with a correlation coefficient of 19.9%. This study is very useful especially for Islamic pawnshops, because the results of this study show the importance of promotion in convincing the public to be interested in becoming customers at the Sumedang Santri Islamic Pawnshop Unit. In addition, this study can also be the basis for decision making in improving the development of the Islamic Pawnshop industry